Kajian Penerapan Peraturan Menteri Pertanian Nomor 53 Tahun 2012 untuk Pengendalian Aflatoksin pada Pala - Ni Made Vina Citanirmala; Winiati Pudji Rahayu; Ratih Dewanti Hariyadi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Nutmeg as Indonesia main exported commodity frequently contaminated by aflatoxin and often rejected by European Union. To improve safety of nutmeg, Ministry of Agricultural (MA) issued a regu- lation number 53 in 2012 regarding good practices on nutmeg. The objectives of this research were to (1) evaluate implementation of the MA regulation at nutmeg supply chain in Siau Barat District (2) identify critical points for mold growth and/or aflatoxin formation along the nutmeg supply chain. This research conducted through (1) surveys to 60 farmers, 10 middlemen, 2 exporters and 3 government officials as respondents; (2) identification of critical steps using HACCP decision trees. The evaluation of MA regu- lation showed that at farmer level was poor for postharvest handling (54.4%) caused by lack of facilities and infrastructure (57.2%), although for harvest was moderate (70.4%). At the middleman level, handling practices at postharvest was moderate (62.5%), although not supported with facilities and infrastructure (36.7%). Handling practices at exporter level was generally good, however supervision at government official level was poor (56.3%). Critical control points determined at farmer level were harvesting and drying, at middlemen level were receiving, drying and storage, while at exporter level were receiving and shipment.